Simulation and Experimental Evaluation of Tensile Properties and Macrostructure Changed of 3D printer PLA Filaments - Syaharuddin Rasyid; Rusdi Nur; Muas Muchtar (Jurnal POLIMESIN, 2022)
The use of printing products with 3D printing has been widely used in everyday life, but research regarding its strength and performance is still limited. Therefore, simulation and experimental approaches are used in this paper to analyze the characteristics of PLA+ materials produced by 3D printers. a. Design tensile test specimens and static stress tests in Autodesk Fusion360; b. Calculate the weight of the tensile test specimen; c. Print tensile test specimens with variations in infill (60, 80, and 100%) and print direction (0, 45, and 90 deg); and d. Experiment with macrostructure, weight, and tensile tests. The conclusions of this study are; a. PLA+ material properties (macrostructure, weight, tensile strength, tensile strain) have been obtained experimentally and through simulation, b. The tensile strength of the simulated PLA+ material is higher than the experimental test results, c. The level of density (infill), affects the weight and tensile strength, and d. The direction of the impression affects the tensile strength, but weight and tensile strain have no effect.